Induction of Peripheral Tolerance in Ongoing Autoimmune Inflammation Requires Interleukin 27 Signaling in Dendritic Cells - Thomé, Rodolfo; Moore, Jason N.; Mari, Elisabeth R.; Rasouli, Javad; Hwang, Daniel; Yoshimura, Satoshi; Ciric, Bogoljub; Zhang, Guang-Xian; Rostami, Abdolmohamad M. (Frontiers in Immunology, 2017)
Peripheral tolerance to autoantigens is induced via suppression of self-reactive lymphocytes, stimulation of tolerogenic dendritic cells (DCs) and regulatory T (Treg) cells. Interleukin (IL)-27 induces tolerogenic DCs and Treg cells; however, it is not known whether IL-27 is important for tolerance induction. We immunized wild-type (WT) and IL-27 receptor (WSX-1) knockout mice with MOG35–55 for induction of experimental autoimmune encephalomyelitis and intravenously (i.v.) injected them with MOG35–55 after onset of disease to induce i.v. tolerance. i.v. administration of MOG35–55 reduced disease severity in WT mice, but was ineffective in Wsx−/− mice. IL-27 signaling in DCs was important for tolerance induction, whereas its signaling in T cells was not. Further mechanistic studies showed that IL-27-dependent tolerance relied on cooperation of distinct subsets of spleen DCs with the ability to induce T cell-derived IL-10 and IFN-γ. Overall, our data show that IL-27 is a key cytokine in antigen-induced peripheral tolerance and may provide basis for improvement of antigen-specific tolerance approaches in multiple sclerosis and other autoimmune diseases.